Análise da atenção básica à saúde do idoso na estratégia saúde da família - ARAÚJO, Maria Aparecida da Silva (2009)
The study focused on the health care of the elderly, more specifically in Family health strategy as a way of thinking about alternatives that allow the reorganization of elderly care to adscritas areas. Processorsthe General was discussing the basic attention actions offered to the elderly in context family health strategy. Search descriptive exploratory in nature,- qualitative basic performed with professionals that comprise health team family doctors, nurses, technicians, nurses and community agents health in the municipality of Aparecida de Goiânia, goaiz. For data collection were the focal group technique and the data were analysed in categories as Bardin. The results suggest that prospects strengthen the professional aspects in family health care to the elderly, while showing some limitations of the elderly in the team. The team's contribution family health was significant health care of the elderly be reconsidered by professionals and managers for the operationalization of education These professional standing. It was concluded that the multidisciplinary actions are present in health promotion, both in the basic unit in address through talks, walks, assistance activities Prevention and control of diseases, although realize difficulties operacionalizá them. The insertion of the elderly in some family health teams occurs through attractive activities forming your social network participation activities outside of the health unit, such as concerts and tours and provide suggestions for activities. However, for other teams actions intersectoral health promotion is not present. The results of this study may offer subsidies to family health professionals for Organization of care to the elderly, to assistance the oldest coherent national policy guidelines of care.